Competitive ability among Eucalyptus spp. commercial clones in Mato Grosso do Sul state - Pavan, Bruno Ettore [UNESP]; Amaral, Rafaela Goularte [UNESP]; Pupin, Silvelise [UNESP]; Costa, Rodolfo Manoel Lemes da; Dias, Donizete da Costa; Scarpinati, Edimar Aparecido; Paula, Rinaldo Cesar de [UNESP] (Elsevier B.V., 2021)
In general, genetic improvement programs for Eucalyptus seek to increase productivity. Diallelic methods are commonly used in crossbreeding designs, but few studies use this methodology to assess competitive ability. The aim of this study was to estimate the competitive capacity and effects of intra- and inter-genotypic in Eucalyptus spp. clones and identify combinations that support increased productivity. To do this, 12 commercial clones were evaluated in a competitive trial located in Tres Lagoas, Mato Grosso do Sul State, Brazil, established in a randomized block design, with three replicates and five plants per plot. Data for the mean annual increment (MAI) obtained at five years of age were assessed using two statistical approaches. Groups were classified according to specific (ability of the two clones to compete each other) and general competitive ability (average ability of a clone to compete with others). There were differences in the genotypes' ability to suffer or exercise competition. The results obtained showed the best combinations resulted in up to 10% increase in productivity. That combined use of diallelic analysis with the statistical approach which allows for the assessment of the effects of intraand inter-clonal competition, may be useful for Eucalyptus spp. improvement programs, especially in terms of identifying the best combinations for planting when the objective is to obtain gains in crop productivity.
Keywords: Inter-clonal competition; Clonal mixture; Competition design; Partial diallel analysis